Clinical Research: From Case Reports to International Multicenter Clinical Trials. Issue 11 (16th August 2021) - Finfer, Simon; Cook, Deborah; Machado, Flavia R.; Perner, Anders
Abstract : Supplemental Digital Content is available in the text.